Market and credit risk as components of bank enterprise risk management - Mohamed, Heba Mohamed (AUC Knowledge Fountain, 2015)
Risk is a very important aspect to consider in the banking sector. The risk model used in the developed economies can be very attractive, but very misleading when used in the emerging economies. This paper analyzes the need for enterprise risk management (ERM) in the banking sector in the emerging economies. Further, it tackles the relationship between market and credit risk in emerging economies banking sector. Despite the technical problems, such as, the lack of historical data to work with in the emerging economies and the markets inefficiency that I faced while doing this paper, this study shows, on a relatively small scale, that market and credit risk affects one another, and proves ERM as a very important tool to enhance risk measurement and supervision in the banking sector. This paper show that despite the fact that not a lot of banks out of my sample crystallize the interaction between market and credit risk, still, they point a number of factors contributing to such outcome. The results end to an important implication that ERM has to be implemented in the emerging economies banking sector, while the current regulatory framework should be changed to accommodate the ERM program.